Revisionary checklist of the Southern African Sesiini (Lepidoptera: Sesiidae) with description of new species - Bartsch, Daniel (Zootaxa, 2013)
A revisionary checklist of the Sesiini of southern Africa is presented. All known genera of the region and their type species are redescribed. The following genera are placed in Sesiini for the first time: Alonina Walker, 1856; Anaudia Wallengren, 1863; Austrosetia Felder & Felder, 1874; Megalosphecia Le Cerf, 1916 and Vespanthedon Le Cerf, 1917. The genera Cicinnoscelis Holland, 1893 rev. stat. (from synonymy with Alonina Walker, 1856) and Felderiola Naumann, 1971 rev. stat. (from synonymy with Monopetalotaxis Wallengren, 1859) are resurrected from synonymy and included in Sesiini. One new genus, Hagnogyna new gen., and seven new species, Cicinnoscelis flavipes new sp., C. krooni new sp., Alonina rufa new sp., A. fusca new sp., Anaudia thyranthrena new sp., Felderiola karooensis new sp. and F. xanthogaster new sp., are described. The following new combinations are introduced: Cicinnoscelis longipes Holland, 1893 rev. comb., Alonina pyrethra (Hampson, 1919) new comb., A. pyrocraspis (Hampson, 1910) new comb., A. luteopunctata (Freina, 2011) new comb., Felderiola candescens (Felder & Felder, 1874) rev. comb., Hagnogyna sanguicosta (Hampson, 1919) new comb., H. bartschi (Freina, 2011) new comb. and Vespanthedon chalciphora (Hampson, 1919) new comb. Alonina difformis Hampson, 1919 new syn. is considered a subjective junior synonym of A. rygchiiformis Walker, 1856. A lectotype is designated for Austrosetia semirufa Felder & Felder, 1874 and the previously unknown males of this species and of Anaudia felderi Wallengren, 1863 are described. Bionomical data for some of the species discussed are given for the first time.